Farm exits and competition on the land market: Evidence from spatially explicit data - Dieter Pennerstorfer (Johannes Kepler University of Linz, Department of Economics, 2022)
In this article, we analyze competition for agricultural land as an important, scarce and immobile input. The cost of cultivating a parcel of land depends strongly on the distance from the farmer to the plot, leading to spatially small land markets. To investigate this issue, we are able to use extremely rich datasets, and combine information on both farms and their cultivated plots (including their exact locations) for virtually all farms in Austria for a five-year period. When analyzing the takeover of parcels from farms leaving the market, we find that the distance between an exiting farm's plot and the closest parcel of a prospective buyer farm is an important determinant of which buyer will prevail on the land market. In addition, the proximity between the farmsteads of the exiting farm and a prospective buyer farm is also important. The results suggest (i) that agricultural land markets are indeed very small and (ii) that information frictions are important in this market.
Keywords: L13; L25; Q12; R14; 330; spatial competition; land market; farm exit; spatial data